Right Ventricular Volumes and Systolic Function by Cardiac Magnetic Resonance and the Impact of Sex, Age, and Obesity in a Longitudinally Followed Cohort Free of Pulmonary and Cardiovascular Disease: The Framingham Heart Study - Foppa, Murilo; Arora, Garima; Gona, Philimon; Ashrafi, Arman; Salton, Carol J; Yeon, Susan B; Blease, Susan J; Levy, Daniel; O'Donnell, Christopher J; Manning, Warren J; Chuang, Michael L (Circulation. Cardiovascular imaging, 2016)
Cardiac magnetic resonance is uniquely well suited for noninvasive imaging of the right ventricle. We sought to define normal cardiac magnetic resonance reference values and to identify the main determinants of right ventricular (RV) volumes and systolic function using a modern imaging sequence in a community-dwelling, longitudinally followed cohort free of clinical cardiovascular and pulmonary disease. The Framingham Heart Study Offspring cohort has been followed since 1971. We scanned 1794 Offspring cohort members using steady-state free precession cardiac magnetic resonance and identified a reference group of 1336 adults (64±9 years, 576 men) free of prevalent cardiovascular and pulmonary disease. RV trabeculations and papillary muscles were considered cavity volume. Men had greater RV volumes and cardiac output before and after indexation to body size (all P<0.001). Women had higher RV ejection fraction than men (68±6% versus 64±7%; P<0.0001). RV volumes and cardiac output decreased with advancing age. There was an increase in raw and height-indexed RV measurements with increasing body mass index, but this trend was weakly inverted after indexation of RV volumes to body surface area. Sex, age, height, body mass index, and heart rate account for most of the variability in RV volumes and function in this community-dwelling population. We report sex-specific normative values for RV measurements among principally middle-aged and older adults. RV ejection fraction is greater in women. RV volumes increase with body size, are greater in men, and are smaller in older people. Body surface area seems to be appropriate for indexation of cardiac magnetic resonance-derived RV volumes.